Femoral neck system vs. cannulated screws on treating femoral neck fracture: a meta-analysis and system review - Zhou, Yimin; Li, Zongyang; Lao, Kecheng; Wang, Zixiu; Zhang, Li; Dai, Shiyou; Fan, Xiao (Frontiers in Surgery, 2023)
Objective This meta-analysis aimed to compare the relative safety and efficacy of cannulated compression screw (CCS) and femoral neck system (FNS) in treating patients with femoral neck fractures and to provide evidence-based medical evidence for FNS in treating femoral neck fractures. Methods PubMed, Embase, Cochrane, and China National Knowledge Infrastructure databases were searched to collect outcomes related to femoral neck fractures treated with FNS and CCS, including time to fracture healing, incidence of non-union, incidence of osteonecrosis of the femoral head, incidence of failure of internal fixation, rate of femoral neck shortening, Harris hip score, Barthel index, operative time, intraoperative blood loss, fluoroscopy frequency, and complications. A meta-analysis was performed using RevManv5.4 (The Cochrane Collaboration) and Stata v14.0 software. Results This analysis included 21 studies involving 1,347 patients. The results showed that FNS was superior to CCS in terms of fracture healing time [mean difference (MD) = −0.75, 95% CI = (−1.04, −0.46), P < 0.05], incidence of bone non-union [odds ratio (OR) = 0.53, 95% CI = (0.29, 0.98), P = 0.04], incidence of osteonecrosis of the femoral head [OR = 0.49, 95% CI = (0.28, 0.86), P = 0.01], incidence of internal fixation failure [OR = 0.30, 95% CI = (0.18, 0.52), P < 0.05], rate of femoral neck shortening [OR = 0.38, 95% CI = (0.27, 0.54), P > 0.05], Harris hip score [MD = 3.31, 95% CI = (1.99, 4.63), P < 0.001], Barthel index [MD = 4.31, 95% CI = (3.02, 5.61), P < 0.05], intraoperative bleeding [MD = 14.72, 95% CI = (8.52, 20.92), P < 0.05], fluoroscopy frequency [OR = 0.53, 95% CI = (0.29, 0.98), P = 0.04], and complications [OR = 0.31, 95% CI = (0.22, 0.45), P < 0.05]. The difference between FNS and CCS in operative time was not statistically significant [MD = −2.41, 95% CI = (−6.88, 2.05), P = 0.29]. Conclusion FNS treatment of femoral neck fracture can shorten the fracture healing time; reduce the incidence and translucent rate of bone non-union, osteonecrosis of the femoral head, and internal fixation failure; reduce intraoperative blood loss and postoperative complications; and improve hip joint function and activity. We are confident in the findings that FNS, an effective and safe procedure for internal fixation of femoral neck fractures, is superior to CCS.